Association Between Social Support and PHQ-4 Scores at a Student-Run Free Clinic - Avaneesh Kunta; Sri Varsha Katoju; Leah Barnes; Oliver Nguyen; Anshul Daga; Gabriel Cartagena; Kartik Motwani; David Feller (Journal of Student-Run Clinics, 2023)
Background: Student-run free clinics (SRFCs) can provide quality mental health care to low-income and uninsured populations who are at a greater risk of depression. Evidence demonstrates the association between social support and severity of depression, but this relationship has not been analyzed in an SRFC. Thus, we assessed the association between social support and depressive symptoms.Methods: We used electronic health records data for patients from 2013-2020 (n=2,501 patients). The dependent variable was severity of depression symptoms as determined by scores on the patient health questionnaire-4 (PHQ-4). Higher PHQ-4 scores correspond to increased severity of depression. The main predictor was the patient's social support, which was defined by their employment status, marital status, and the number of individuals in their household. We conducted a multinomial regression model to control for other patient-level factors (i.e. race, sex, and age).Results: When controlling for other factors, patients with higher social support scores had lower odds of scoring a 4 on the PHQ-4 (Odds ratio [OR]=0.838, 95% Confidence interval (CI)=0.770-0.912). When examining specific social support sources, when compared to patients who reported being not-married, those who were married had lower odds of scoring a 4 on the PHQ-4 (OR=0.578, 95% CI=0.401-0.833). Compared to patients who reported being employed, those who were unemployed had greater odds of scoring a 4 on the PHQ-4 (OR=2.323, 95% CI=1.766-3.055). We observed no significant differences in PHQ-4 by the number of people in the household.Conclusion: Patients with greater social support were associated with fewer depressive symptoms. Specifically, employment status and marital status may be larger contributors to a patient’s social support. Our results allow SRFCs to offer interventions such as investing in social work programs and community partnerships that offer professional development and employment opportunities to patients.This article contains a correction, doi: 10.59586/jsrc.v9i1.345.g357.